2019
DOI: 10.1111/ecog.04762
|View full text |Cite
|
Sign up to set email alerts
|

At what spatial scale(s) do mammals respond to urbanization?

Abstract: Spatial scale is fundamental in understanding species-landscape relationships because species' responses to landscape characteristics typically vary across scales. Nonetheless, such scales are often unidentified or unreliably predicted by theory. Many landscapes worldwide are urbanizing, yet the spatial scaling of species' responses to urbanization is poorly understood. We investigated the spatial scaling of urbanization effects on a community of 15 mammal species using ~60 000 wildlife detections collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 79 publications
3
39
1
Order By: Relevance
“…No two land-cover covariates included in our top models for individual species exhibited the same scale of effect. Although past studies have identi ed many urban taxa, such as birds (Hostetler and Holling 2000, Pennington and Blair 2011, Hallman and Robinson 2020) and arthropods (Bennett and Gratton 2012) as responding to the environment at multiple spatial scales, our results support recently described evidence for similar multi-scale relationships between mammal species and urban environments (Moll et al 2020). Additionally, and in line with our expectations, of the nine scales of effect examined across these three species, we found only one shared scale of effect across species (fox squirrel and opossum), for impervious surface coverage at 100 meters.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…No two land-cover covariates included in our top models for individual species exhibited the same scale of effect. Although past studies have identi ed many urban taxa, such as birds (Hostetler and Holling 2000, Pennington and Blair 2011, Hallman and Robinson 2020) and arthropods (Bennett and Gratton 2012) as responding to the environment at multiple spatial scales, our results support recently described evidence for similar multi-scale relationships between mammal species and urban environments (Moll et al 2020). Additionally, and in line with our expectations, of the nine scales of effect examined across these three species, we found only one shared scale of effect across species (fox squirrel and opossum), for impervious surface coverage at 100 meters.…”
Section: Discussionsupporting
confidence: 86%
“…Models that fail to account for scale of effect and rely on a single spatial scale selected a priori can mischaracterize the strength and direction of relationships (Miguet et al 2016, Moll et al 2020, or nd no relationship where one may truly exist over a smaller or bigger spatial extent than used in modeling (Holland and Yang 2016). For example, multiple studies have reported a negative relationship between coyote (Canis latrans) occupancy and urban intensity as measured by housing density (Fidino et al 2020) or proportional impervious cover (Wait et al 2018) within 1 km buffers, yet a study that measured urban intensity over a larger extent (3 km) identi ed a positive relationship (3 km, Ordeñana et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These traits may be important for predicting space use within urban areas, but not urban tolerance as measured in our current analysis. Future work should formally test how species-specific responses to urbanization varies among spatial scales in butterflies (e.g., Moll et al 2020;Callaghan et al 2020). In addition to our limitations in the spatial resolution, we highlight that we only looked at urban preferences in butterflies averaged across the full annual cycle, but some species may increase their use of urban areas during certain times of the year.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that via the presentation of this typological framework ( Figure 1 ), we are not presuming directionality of animal responses. While many animal species are negatively affected by human activity, others experience positive feedbacks [ 7 ]. Additionally, the COVID-19 pandemic triggered a series of complex direct and indirect effects on animal populations and the environment [ 8 ].…”
Section: Typology Of Animal Behavioral Responsesmentioning
confidence: 99%